Pyridinium-2-carbaldoximes with quinolinium carboxamide moiety are simultaneous reactivators of acetylcholinesterase and butyrylcholinesterase inhibited by nerve agent surrogates - Lee, Hyun Myung; Andrys, Rudolf; Jonczyk, Jakub; Kim, Kyuneun; Vishakantegowda, Avinash G; Malinak, David; Skarka, Adam; Schmidt, Monika; Vaskova, Michaela; Latka, Kamil; Bajda, Marek; Jung, Young-Sik; et al. (Journal of enzyme inhibition and medicinal chemistry, 2021)
The pyridinium-2-carbaldoximes with quinolinium carboxamide moiety were designed and synthesised as cholinesterase reactivators. The prepared compounds showed intermediate-to-high inhibition of both cholinesterases when compared to standard oximes. Their reactivation ability was evaluated in vitro on human recombinant acetylcholinesterase (hrAChE) and human recombinant butyrylcholinesterase (hrBChE) inhibited by nerve agent surrogates (NIMP, NEMP, and NEDPA) or paraoxon. In the reactivation screening, one compound was able to reactivate hrAChE inhibited by all used organophosphates and two novel compounds were able to reactivate NIMP/NEMP-hrBChE. The reactivation kinetics revealed compound 11 that proved to be excellent reactivator of paraoxon-hrAChE better to obidoxime and showed increased reactivation of NIMP/NEMP-hrBChE, although worse to obidoxime. The molecular interactions of studied reactivators were further identified by in silico calculations. Molecular modelling results revealed the importance of creation of the pre-reactivation complex that could lead to better reactivation of both cholinesterases together with reducing particular interactions for lower intrinsic inhibition by the oxime.
Keywords: oxime; Cholinesterase Inhibitors; Recombinant Proteins; Structure-Activity Relationship; reactivator; molekulární struktura; Molecular Structure; chinolinové sloučeniny; vztah mezi dávkou a účinkem léčiva; Organophosphate; Molecular Docking Simulation; acetylcholinesterase; acetylcholinesterasa; Pyridinium Compounds; vztahy mezi strukturou a aktivitou; Quinolinium Compounds; simulace molekulového dockingu; rekombinantní proteiny; pyridinové sloučeniny; lidé; Humans; Butyrylcholinesterase; butyrylcholinesterasa; Acetylcholinesterase; cholinesterasové inhibitory; Dose-Response Relationship, Drug; butyrylcholinesterase